2018
DOI: 10.1007/s40256-018-0272-5
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Hypertension: Combination Therapy in Practice

Abstract: Combination therapy is now regarded as the standard of care in pulmonary arterial hypertension (PAH) and is becoming widely used in clinical practice. Given the inherent complexities of combining medications, there is a need for practical advice on implementing this treatment strategy in the clinic. Drawing on our experience and expertise, within this review, we discuss some of the challenges associated with administration of combination therapy in PAH and how these can be addressed in the clinic. Despite thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 35 publications
0
57
0
2
Order By: Relevance
“…In line with findings in the AMBITION trial,12 peripheral oedema was more common with combination therapy than monotherapy. In patients receiving multiple therapies, a greater number of side effects compared with patients undergoing single therapy are possible, particularly therapies associated with vasodilation 32…”
Section: Discussionmentioning
confidence: 99%
“…In line with findings in the AMBITION trial,12 peripheral oedema was more common with combination therapy than monotherapy. In patients receiving multiple therapies, a greater number of side effects compared with patients undergoing single therapy are possible, particularly therapies associated with vasodilation 32…”
Section: Discussionmentioning
confidence: 99%
“…An early positive treatment response, with improvement of clinical, functional, and haemodynamic parameters [1], has been shown to result in a similar survival benefit as having a stable low-risk profile at the time of diagnosis [2, 2022]. Thus, access to several treatment options and better understanding of treatment strategies, including the benefits of combination therapy [23, 24], might have contributed to reducing, not only the total mortality, but also the sex-related differences in survival seen in previous studies [25]. It has been suggested that women may benefit more from ERAs than men and that men may benefit more from a PDEi than women [25, 26]; however, findings from studies with a direct comparison between an ERA and PDEi did not support this [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…The practical application of combination therapy in PAH has recently been summarized. 19 Among other useful points is that all PAH patients may not tolerate the simultaneous initiation of a PDE-5 inhibitor and an endothelin receptor antagonist, that is, combination therapy may need to be initiated in a stepped approach. For those patients intolerant of oral IP receptor agonists, for example, in whom an oral IP receptor was initiated because of a decrease in 6MWD or an increase in NTproBNP as opposed to progression to functional Class IV, the clinician can consider a trial of either inhaled treprostinil or iloprost to improve functional capacity.…”
Section: Summary and Thoughtsmentioning
confidence: 99%